Knowledge society in the midst of a society of ignorance - Lara González, José David (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This paper argues the fallacy of assuming today's society as the society of knowledge, means and purpose of the project of globalization of the whole world. It supports the presence of current phenomena of the information society and knowledge economy. From critical theory postulates the difference between knowledge and learning and the functional role that science and technology have for the dominant system imposed by neoliberal capitalism. It is noted some differences between the existing real society and the virtual society that has been generated. It also states that the knowledge society is populated by ignorance and acknowledge.
Keywords: globalization; critical theory; modernity; education; technological transformation.